Design and operation of a therapeutic unit with unsealed radioactive sources - Papadopoulos, A.; Dristiliaris, D.; Tsiouris, S.; Fotopoulos, A.; Kalef-Ezra, J. (HNPS Advances in Nuclear Physics, 2019)
A radioisotope therapeutic unit (RTU) for the treatment of patients with radiopharmaceuticals was designed and set in operation by the Ioannina University Hospital Medical Physics and Nuclear Medicine Departments. A number of parameters and procedures have been taken into account during the design stage to combine high quality medical services with minimum unjustified radiation exposures. Two pre-existing wards were modified to therapy / isolation wards by the addition of structural shielding made of concrete or/and iron and lead plates. Similar modifications were carried out in some of the remaining rooms of the RTU, such as the corresponding hot-lab and the storage-to-decay rooms. A network of GM detectors was installed for continuous monitoring of radiation levels at various locations. Among the first one hundred patients treated at the Unit, 80 had differentiated cancer and 14 had hyperthyroidism and were treated with 131I of activity ranging between 0.74 and 7.4 GBq. The maximum H*(10) rate at 1.0 m distance from the patient’s body was one of the criteria for patient release and was set on patient-specific terms. The adequacy of the RTU design and the employed operational policies were verified in practice. In conclusion, the RTU meets successfully the predicted needs.